2002
DOI: 10.1243/095440502320193012
|View full text |Cite
|
Sign up to set email alerts
|

Wear evaluation of a self-propelled rotary tool when machining titanium alloy IMI 318

Abstract: This paper presents results of a self-propelled rotary tool (SPRT) tipped with round uncoated carbide (WC-Co) inserts in the finish turning of titanium alloy IMI 318. SPRT inserts exhibited superior wear resistance to conventional round and rhomboid-shaped carbides as well as to the rhomboid-shaped physical vapour deposition (PVD) TiN-coated carbide inserts owing to the distribution of the cutting energy along the entire tool edge. The SPRT-tipped inserts suppressed thermally related wear mechanisms at higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
0
8
0
1
Order By: Relevance
“…In general, when machining steel with coated carbide tools, different tool wear mechanisms occur, such as abrasion, adhesion, oxidation and even some diffusion, which act simultaneously and in proportions depending mainly on the temperature as suggested by Usui. 10 Ezugwu et al 11 have found that temperature can reach up to 1500°C during machining of stainless steel with carbide tool in conventional lathe. Therefore, water-based fluid is widely used to dissipate the heat in order to reduce the strength of the cutting tool, leading to tool failure by diffusion wear.…”
Section: Introductionmentioning
confidence: 99%
“…In general, when machining steel with coated carbide tools, different tool wear mechanisms occur, such as abrasion, adhesion, oxidation and even some diffusion, which act simultaneously and in proportions depending mainly on the temperature as suggested by Usui. 10 Ezugwu et al 11 have found that temperature can reach up to 1500°C during machining of stainless steel with carbide tool in conventional lathe. Therefore, water-based fluid is widely used to dissipate the heat in order to reduce the strength of the cutting tool, leading to tool failure by diffusion wear.…”
Section: Introductionmentioning
confidence: 99%
“…Kishawy and Wilcox [7] studied tool wear and chip formation during hard turning with self-propelled rotary cutting tools and they reported that self-propelled tools showed good resistance to tool wear compared with stationary cutting tools under the same cutting conditions. Ezugwu et al [8] investigated wear evaluation using self-propelled rotary cutting tool in machining of titanium alloy IMI 318 and rotary cutting tool exhibited superior wear resistance to conventional stationary cutting tools. Kishawy et al [9] studied on tool performance and machined surface quality during the machining of aerospace alloys using self-propelled rotary cutting tools and they obtained optimum and safe cutting conditions.…”
Section: Figure 2 a Rotary Cutting Toolmentioning
confidence: 99%
“…1. Nóż SPRT w imaku narzędziowy tokarki (a), widok strefy skrawania (b) dzonych w kraju i na świecie [2,3,4,5,6] wskazują na potrzebę oparcia takich badań na klasycznych geometrycznych kryteriach zużycia i trwałości narzędzia rejestrowanych na powierzchni natarcia (krater) i przyłożenia ostrza (starcie), przy czym zużycie powierzchni przyłożenia wydaje się częściej stosowanym i przydatniejszym w analizach porównawczych wyników zaczerpniętych z różnych prac [3,4,5,6]. …”
Section: Model Zużycia Noży Z Ostrzem Samoobrotowym W Obróbce Materiaunclassified